Translanguaging in Virtual Class - Yusuf Al Arief (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Many teachings and learning are still applying hybrid learning and several university classes are still conducted online after of the Covid-19 outbreak, and one of the ways was online video conferences to accommodate the need for face-to-face learning. However, distant learning resulted in the loss of metalanguage features that usually support classroom interaction. This research aimed to determine the Translanguaging applicability and benefits for teaching and learning since the metalanguage features were absent from the class interaction. The method used was descriptive, and the approach applied was qualitative. It was found that Translanguaging practice for the online video conference benefits both lecturers and students. It benefits teaching and learning by creating a good learning atmosphere and provides the same experience between online and offline teaching and learning processes. For the lecturers, Translanguaging helped them to simplify difficult materials explanation and bridge the communication with the students. In addition, it also benefits the students, such as handling technical issues, providing chances to share new vocabulary, and dodging misunderstanding of the lesson explanation. To conclude, implementing translanguaging in online video conference classes benefits and fits the students' learning needs.